2016
DOI: 10.1080/02648725.2017.1307673
|View full text |Cite
|
Sign up to set email alerts
|

Outlook in the application ofChlamydomonas reinhardtiichloroplast as a platform for recombinant protein production

Abstract: Microalgae, also called microphytes, are a vast group of microscopic photosynthetic organisms living in aquatic ecosystems. Microalgae have attracted the attention of biotechnology industry as a platform for extracting natural products with high commercial value. During last decades, microalgae have been also used as cost-effective and easily scalable platform for the production of recombinant proteins with medical and industrial applications. Most progress in this field has been made with Chlamydomonas reinha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…C. reinhardtii has gained significant applications in the biotechnological industry, becoming a platform for obtaining natural products of very high commercial value. The chloroplast of C. reinhardtii could be used as a platform for recombinant protein production (Shamriz & Ofoghi, 2016). Moreover, C. reinhardtii has applications in the production of biohydrogen (Xu, Fan, & Wang, 2019), which could potentially be used in hydrogen fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…C. reinhardtii has gained significant applications in the biotechnological industry, becoming a platform for obtaining natural products of very high commercial value. The chloroplast of C. reinhardtii could be used as a platform for recombinant protein production (Shamriz & Ofoghi, 2016). Moreover, C. reinhardtii has applications in the production of biohydrogen (Xu, Fan, & Wang, 2019), which could potentially be used in hydrogen fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae such as the unicellular green alga C. reinhardtii have many advantages that make them ideal for recombinant protein production [ 47 , 48 ]. However, low yield and inefficient downstream processing are the main obstacles to engineering algae strains for industrialisation [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most studied microalgae for genetic engineering, C. reinhardtii is widely used as an algal recombinant expression platform for biomedical applications. 34 A novel approach using transgenic C. reinhardtii was developed to produce oxygen and proangiogenic growth factors such as human vascular endothelial growth factor A (hVEGF-165) to promote wound healing in biomedical settings. 35 The study identified the optimal combination of C. reinhardtii and protein expression elements to produce recombination proteins in a high-efficiency model.…”
Section: Eukaryote Microalgaementioning
confidence: 99%